Psychological and pedagogical support of tourist travel as a process of familiarization with the civilizational heritage - Kuznetsova, N.V.; Suleimen, S.B.; Arpentieva, M.R.; Kassymova, G.K.; Xu, Wenxin; Fang, Yuqi (Universitas Negeri Yogyakarta, 2024)
The study of tourism psychological and educational issues and the development and implementation of tourism psychological and educational support are still an area of relatively little theoretical and applied research. At the same time, tourism is not just a leisure activity, but a transformative experience that can profoundly change personal and social identity, serve the development of the individual, and change the needs of the individual as a